The performance of students with and without disability on the 11th grade university admission test (2013)
Objective Comparing standardized university admission scores between students with and without disability within the same school and also comparing the performance of students with hearing, visual and physical disability.Methods This was a retrospective cohort study which compared the test results of students with and without disabilities within the same school. A matched case-control study nested in a cohort was assembled. Standardized differences were calculated for comparing such scores.Results Students without disabilities performed significantly better than disabled ones(i.e. disabled students scored lower than their classmates).Conclusion Further research is needed to determine whether the Colombian educational system, adjustments made to tests for this population or students’ individual skills were the factors underlying the difference regarding the test results.